2020
DOI: 10.3382/ps/pez567
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a selected yeast fraction on the prevention of pullorum disease and fowl typhoid in commercial breeder chickens

Abstract: A selected yeast fraction ( SYF ) was tested for the purpose of preventing pullorum disease and fowl typhoid in breeder chickens. In a challenge-protection experiment, commercial Three-Yellow breeder chicks were initially divided into groups A, B (challenged, treated), C (challenged, untreated), and D (unchallenged, untreated). The group A diet was supplemented with SYF and group B was supplemented with Acidipure via drinking water. At 7 D, birds of groups A, B, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…The results of this study showed that more birds were positive for Salmonella pullorum in the samples of mixed organs and cecum when compared with the sample of cloaca swabs in the challenged/untreated subgroup B1, and the same trend was also observed in the Salmonella give - and Salmonella kentucky -challenged groups B2 and B3. These results are in agreement with previous study [ 26 ]. Salmonella exhibited a high affinity for the intestinal tract, especially the cecum and ileocecal junction.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of this study showed that more birds were positive for Salmonella pullorum in the samples of mixed organs and cecum when compared with the sample of cloaca swabs in the challenged/untreated subgroup B1, and the same trend was also observed in the Salmonella give - and Salmonella kentucky -challenged groups B2 and B3. These results are in agreement with previous study [ 26 ]. Salmonella exhibited a high affinity for the intestinal tract, especially the cecum and ileocecal junction.…”
Section: Discussionsupporting
confidence: 94%
“…Salmonella infection generally cause a range of symptoms, including pasty diarrhea, anorexia, emaciation, depression, and even death in very young chicks or poults, which is infrequent in mature poultry [ 26 , 32 ]. In this study, birds in the challenged/untreated groups exhibited weakness, poor growth, white diarrhea, anal paste, and severe liver and heart lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kiarie et al [ 13 ] revealed that when added with feed enzymes, yeast derivatives can modulate cellular- and humoral-mediated immunity in broilers against intestinal coccidial infections. Zhou et al [ 14 ] investigated the ability of yeast fractions to prevent pullorum disease and fowl typhoid in breeders. The results of the study revealed that dietary fortification of yeast fractions significantly reduced disease infection in the challenged breeders.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study revealed that dietary fortification of yeast fractions significantly reduced disease infection in the challenged breeders. In the same study, the positive culling rate of the pullets and their body weight were significantly reduced because of the addition of yeast fractions to the feed of birds challenged with Salmonella infection [ 14 ]. The intestinal microflora balance has also been shown to be improved in birds with dietary supplementation of yeast, due to the presence of mannan-oligosaccharides and fructo-oligosaccharides in the cell wall of yeast [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PD has been eradicated from commercial poultry in many developed countries, owing to the introduction of pullorum-typhoid programs based on detection and elimination of the affected birds ( Barrow and Freitas Neto, 2011 ). However, the PD remains a big threat to the poultry industry in developing countries and causes serious economic loss every year ( Eriksson et al., 2018 ; Zhou et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%